Trends in antimicrobial resistance in bloodstream infection isolates at a large urban hospital in Malawi (1998–2016): a surveillance study. Issue 10 (October 2017) - Musicha, Patrick; Cornick, Jennifer E; Bar-Zeev, Naor; French, Neil; Masesa, Clemens; Denis, Brigitte; Kennedy, Neil; Mallewa, Jane; Gordon, Melita A; Msefula, Chisomo L; Heyderman, Robert S; Everett, Dean B; et al.
Summary: Background: Bacterial bloodstream infection is a common cause of morbidity and mortality in sub-Saharan Africa, yet few facilities are able to maintain long-term surveillance. The Malawi-Liverpool-Wellcome Trust Clinical Research Programme has done sentinel surveillance of bacteraemia since 1998. We report long-term trends in bloodstream infection and antimicrobial resistance from this surveillance. Methods: In this surveillance study, we analysed blood cultures that were routinely taken from adult and paediatric patients with fever or suspicion of sepsis admitted to Queen Elizabeth Central Hospital, Blantyre, Malawi from 1998 to 2016. The hospital served an urban population of 920 000 in 2016, with 1000 beds, although occupancy often exceeds capacity. The hospital admits about 10 000 adults and 30 000 children each year. Antimicrobial susceptibility tests were done by the disc diffusion method according to British Society of Antimicrobial Chemotherapy guidelines. We used the Cochran-Armitage test for trend to examine trends in rates of antimicrobial resistance, and negative binomial regression to examine trends in icidence of bloodstream infection over time. Findings: Between Jan 1, 1998, and Dec 31, 2016, we isolated 29 183 pathogens from 194 539 blood cultures. Pathogen detection decreased significantly from 327·1/100 000 in 1998 to 120·2/100 000 in 2016 (p<0·0001). 13 366 (51·1%) of 26 174 bacterial isolates were resistant to the Malawian first-line antibiotics amoxicillin or penicillin, chloramphenicol, and co-trimoxazole; 68·3% of Gram-negative and 6·6% of Gram-positive pathogens. The proportions of non- Salmonella Enterobacteriaceae with extended spectrum beta-lactamase (ESBL) or fluoroquinolone resistance rose significantly after 2003 to 61·9% in 2016 (p<0·0001). Between 2003 and 2016, ESBL resistance rose from 0·7% to 30·3% in Escherichia coli, from 11·8% to 90·5% in Klebsiella spp and from 30·4% to 71·9% in other Enterobacteriaceae. Similarly, resistance to ciprofloxacin rose from 2·5% to 31·1% in E coli, from 1·7% to 70·2% in Klebsiella spp and from 5·9% to 68·8% in other Enterobacteriaceae. By contrast, more than 92·0% of common Gram-positive pathogens remain susceptible to either penicillin or chloramphenicol. Meticillin-resistant Staphylococcus aureus (MRSA) was first reported in 1998 at 7·7% and represented 18·4% of S aureus isolates in 2016. Interpretation: The rapid expansion of ESBL and fluoroquinolone resistance among common Gram-negative pathogens, and the emergence of MRSA, highlight the growing challenge of bloodstream infections that are effectively impossible to treat in this resource-limited setting. Funding: Wellcome Trust, H3ABionet, Southern Africa Consortium for Research Excellence (SACORE).